Using stepwise backward elimination to specify terms related to tactile sense for product design. (October 2020) - Hsu, Fang-Chen; Chen, Chien-Nan; Shieh, Meng-Dar
Highlights: The representative vocabularies of the tactile sense for materials are collected to facilitate communication between designers and consumers. Imprecise and ambiguous terms are discarded individually using reliability analysis and stepwise backward elimination. The efficacy of the identified terms was evaluated in an experiment using real-world materials in a manner that focused solely on the sense of touch. Abstract: The tactile sense plays a crucial role in the evaluation of products by providing important information pertaining to the material properties of the products. Designers must reach a consensus with target consumers regarding the perception of touch and the terms used to describe it. In this paper, Cronbach's alpha (used in reliability analysis) and the Kaiser-Meyer-Olkin test (used in factor analysis) are proposed to consider in assembling a reliable set of sensory terms applicable to the description of consumer products. Stepwise backward elimination is used to eliminate ambiguous and imprecise terminology in order to derive highly specific words that are representative of the tactile sense. Factor analysis is then used to assign the resulting terms to two categories: material strength and surface texture . These two categories are classified to the evaluation dimension proposed by Osgood et al. (1957) [1]. This study departed from many previous works in eliminating the visual sense from all analysis. The resulting terms provide a valuable reference for the selection of materials and act as a guide to communication with potential consumers.